LncRNA BC200 Promotes Esophageal Squamous Cell Cancer Migration and Invasion and Can Regulate ATF4 Expression - Zhao, Ruihua; Cao, Xinguang; Jin, Shuiling; Li, Rui; Zhong, Qian; Jiang, Miao; Han, Jinming; Guo, Changqing; Zong, Hong (Frontiers in Oncology, 2020)
Background: The main reason for esophageal squamous cell carcinoma (ESCC) treatment failure is metastasis. Little is known about the mechanisms involved in the metastasis of ESCC, there is a lack of effective therapeutic targets. In our previous study, we found that patients with high levels of BC200 tended to have poor prognoses. Methods: First, we applied qRT-PCR to detect the expression of BC200 in normal esophageal squamous epithelial cells and ESCC cells with different degrees of differentiation ability. Then, we changedBC200 expression by transfecting constructed lentiviruses that included BC200 shRNA (LV-BC200-shRNA, KD, negative control (CON053, NC) or BC200 gene (LV-BC200, BC200) to create BC200-deficient cell models in KYSE410 and KYSE70 cells and BC200 overexpression cell models in EC9706 cells and verified the transfection effect by qRT-PCR. Then, we examined cell migration by wound healing assay, invasion by Transwell assay, and proliferation by MTT assay and examined the metastasis ability in a xenograft mouse model. Gene expression profiling was performed to screen a panel of mRNAs following inhibition of BC200 expression. We then used ingenuity pathway analysis (IPA) to analyze the functions of the changed molecules and their interactions. The results from the microarray were validated by qRT-PCR and western blotting. Result: In this study, we found that the expression of BC200 in poorly differentiated cell lines was significantly higher than that in well-differentiated cell lines. BC200 can significantly promote the migration and invasion but not the proliferation ability of ESCC cells in vitro and BC200 shRNA can significantly suppress tumor metastasis in vivo. Our genome-wide expression profile chip showed 406 differentially expressed genes, with 91 upregulated genes and 315 downregulated genes. The upstream regulator analysis showed that ATF4 was predicted to be strongly inhibited and 21 genes were consistently inhibited by this gene. Our qRT-PCR and western blotting data also identified the reduced expression of ATF4 and some selected downstream genes, such as SNAIL2, GADD45A, and PSAT1, as a consequence of downregulating BC200 expression in ESCC. Conclusion: Our data showed that BC200 promoted the metastasis of ESCC cells and could regulate the expression of ATF4 and its downstream genes.